Development of an HTS-Compatible Assay for Discovery of Melanoma-Related Microphthalmia Transcription Factor Disruptors Using AlphaScreen Technology. (January 2017) - Wang, Jing; Fang, Pengfei; Chase, Peter; Tshori, Sagi; Razin, Ehud; Spicer, Timothy P.; Scampavia, Louis; Hodder, Peter; Guo, Min
Microphthalmia transcription factor (MITF) is a master transcription factor expressed in melanocytes, essential for melanocyte survival, differentiation, and pigment formation, and is a key oncogenic factor in melanoma initiation, migration, and treatment resistance. Although identified as an important therapeutic target for melanoma, clinical inhibitors directly targeting the MITF protein are not available. Based on the functional state of MITF, we have designed an MITF dimerization-based AlphaScreen (MIDAS) assay that sensitively and specifically mirrors the dimerization of MITF in vitro. This assay is further exploited for identification of the MITF dimer disruptor for high-throughput screening. A pilot screen against a library of 1280 pharmacologically active compounds indicates that the MIDAS assay performance exhibits exceptional results with a Z′ factor of 0.81 and a signal-to-background (S/B) ratio of 3.92 while identifying initial hit compounds that yield an ability to disrupt MITF-DNA interaction. The results presented demonstrate that the MIDAS assay is ready to screen large chemical libraries in order to discover novel modulators of MITF for potential melanoma treatment.